[Proceedings] 1990 IEEE 7th International Symposium on Applications of Ferroelectrics
DOI: 10.1109/isaf.1990.200325
|View full text |Cite
|
Sign up to set email alerts
|

Relaxor based fine grain piezoelectric materials

Abstract: The dielectric and piezoelectric properties of polycrystalline ceramics of relaxor ferroelectric lead magnesium niobate-lead titanate modified with La2O3, (l-x)(Pbo.~5Lao.oi~o.o05(Mgi/3N b2/3)-(x)PbTi03, h a v e been investigated. The compositional range of 0.2 5 x 5 0.4, being near the morphotropic phase boundary, was characterize d.Lanthanum doping resulted in reduction of grain size, enhanced density, and shifted t h e dielectric maximum t e m p e r a t u r e downwardly.The final microstructures of all comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Similarly, Kim et al [17] reported that La-doping at\1 mol% resulted in the decrease in the grain size of PMN and PMN-PT ceramics. The behavior was explained by solid-solution impurity drag mechanism [17].…”
Section: Microstructural Evolutionmentioning
confidence: 81%
See 2 more Smart Citations
“…Similarly, Kim et al [17] reported that La-doping at\1 mol% resulted in the decrease in the grain size of PMN and PMN-PT ceramics. The behavior was explained by solid-solution impurity drag mechanism [17].…”
Section: Microstructural Evolutionmentioning
confidence: 81%
“…They interpreted their observations such that using La +3 based admixture determines the incorporation of the La +3 on the Pb +2 site acting as the donor dopant [2]. Similarly, Kim et al [17] reported that La-doping at\1 mol% resulted in the decrease in the grain size of PMN and PMN-PT ceramics. The behavior was explained by solid-solution impurity drag mechanism [17].…”
Section: Microstructural Evolutionmentioning
confidence: 92%
See 1 more Smart Citation
“…This last effect was the first to be exploited, in the realization of actuators as speakers, but recently is being studied for the possibility of applying piezoelectric materials in contact with vibration sources to recover energy from them. For this purpose, more efficient piezoelectric materials, such as lead zirconate titanate (PZT) [26,27] or relaxor-based ferroelectric single crystals, have been studied [28].…”
Section: Introductionmentioning
confidence: 99%